Odontogenic cervicofacial cellulitis in rural area - Tamassi Bertrand Essobiyou; Solim Uziel Roselin Boko; Geremie Ananidjin; Michel Fabien Dargani; Samuel Salem Laurent Ouedraogo; Saliou Adam; Haréfétéguéna Bissa (Elsevier, 2023)
Objective: To describe the epidemiological, diagnostic and therapeutic aspects of odontogenic cervicofacial cellulitis in rural Togo, and more specifically in the town of Dapaong. Method: This was a monocentric, retrospective, descriptive study conducted at the Dapaong regional hospital over 03 years from January 2019 to December 2021. Results: A total of 103 cases were collected, representing an annual frequency of 34.33 cases per year. The mean age of the patients was 45.69 ± 17.49 years. We reported a male predominance, with a male/female sex ratio of 2.03. We had high exposure to risk factors for cervicofacial cellulitis (92.23%), with HIV infection predominating. Anti-inflammatory drugs and traditional therapy concerned 43.68% and 48.54% of our sample respectively. The average consultation time was 16.17 ± 7.42 days. Pain (100%) and swelling (84.46%) were the clinical signs most frequently encountered. Involvement was predominantly hemifacial, with diffuse cellulitis predominating (56.31%). The maxillary molars (38.83%) were the main site of infection. Resuscitation and triple antibiotic therapy concerned 23.30% of patients, and surgery 59.22%. The in-hospital mortality rate for odontogenic cervicofacial cellulitis in our study was 11.65%. Conclusion: Although odontogenic cervicofacial cellulitis is uncommon in the town of Dapaong, it is associated with a delay in treatment and a high mortality rate.